An Experimental Validated Computational Method for pKa Determination of Substituted 1,2-Dihydroxybenzenes - Romero, Romina; Salgado, Pablo R.; Soto, César; Contreras, David; Melin, Victoria (Frontiers in Chemistry, 2018)
1, 2-dihydroxybenzenes (DHBs) are organic compounds widely studied for being applied in advanced oxidation processes. These compounds are also related to the develop of oxidative stress, wood biodegradation, neuronal disease in humans. DHBs are metal ligands with pro-oxidant and antioxidant properties. These activities are related with their chelation properties and in consequence with the deprotonation of their hydroxyl groups. In literature, there are several pKa values for the hydroxyl groups of DHBs. These values vary depending on the experimental conditions or the algorithm used for calculation. In this work, a computational method experimentally validated was implemented in aqueous solution for pKa determination of 24 DHBs. The selective deprotonation of the hydroxyl groups was determined and related with the electron withdrawing or donating properties of the substituents of the ring.